Factors influencing children's readiness for school entry - Glamočak, Sandra; Uzelac, Jovana; Golubović, Špela (Norma, 2025)
Starting school represents an important milestone in every child's development, and school readiness is determined by a combination of various factors. It does not only involve acquiring certain knowledge and skills but also implies the child's overall preparedness for the school environment. The aim of this paper is to identify and analyze the key factors influencing school readiness through a narrative review of empirical and review studies. The theoretical framework of the paper is the Ecological Systems Theory, which enables a comprehensive understanding of the reciprocal influences of various systems on child development. Literature was gathered using the Google Scholar, PubMed, and Web of Science databases. Both empirical and review studies were included in the analysis. The literature review showed that there are numerous factors that can have either a positive or negative impact on school readiness, relating to the child, the family, and the school system. The analyzed results indicate that school readiness cannot be viewed in isolation but rather as an outcome of multiple interrelated factors—from the child’s cognitive and emotional abilities, through parental involvement and the family’s socio-economic status, to the support offered by the school system through prepared teachers and a stimulating environment. These findings can serve as guidelines for improving policies and practices related to preparing children for school, enabling a smoother transition and better conditions for success in the school setting. This underscores the importance of coordinated action by all stakeholders involved in the process of early education and development.
Keywords: school readiness; family; school system; perspectives; skills